(untitled) (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Despal, Faresty C, Zahera R, Toharmat R. 2022. Title The feeding behavior of dairy cattle under tropical heat stress conditions at smallholder urban farming. Biodiversitas 23: 3771-3777. Dairy cattle (Bos taurus) feeding behavior influences feed intake and affect animal welfare and disease management. This study observed dairy cattle feeding behaviors under tropical smallholder urban farming environments. Thirty-six cattle at the Kebon Pedes area of Bogor City were observed during 12 h feeding (6 am-6 pm). These traits included eating, ruminating, resting duration, and frequencies, measured using a continuous method. Temperature, humidity, temperature-humidity index (THI), feed and nutrient intake, milk production, and components were measured. The results showed that the cattle were in mild to severe heat stress. The average cow daily eating, ruminating, and resting frequencies were 6.61, 7.61, and 22.33 times, while the average eating, ruminating, and resting durations per cow per 12 h were 129.64, 105.67, and 484.69 minutes, respectively. The dry matter intake was 11.17 kg with a roughage to concentrate ratio of 0.73:1. The protein, ash, ether extract, and crude fiber intake were 10.25, 6.62, 3.67, and 22.08% DM, respectively. The average milk productions and fat contents were 11.01 L/head/d and 5.44%. The results showed that eating and ruminating levels correlated positively with feed, and CF intakes while resting correlated negatively. It was concluded that the cattle were in heat-stressed (THI of >78) condition, reduced DM intake, and deficient in energy and CP, which led to lower milk production but higher milk components, specifically milk fat. It is recommended to improve forage quality that promotes eating and ruminating and reduces resting durations, improving milk production.